Hospitalizations and mortality of patients with heart failure in the COVID-19 era in Peru - Hernández-Vásquez, Akram (2022)
Objectives: The worldwide heart failure (HF) prevalence is 8.52 per 1000 inhabitants, with a global economic burden of 346.17 billion dollars. With the COVID-19 pandemic, the focus of medical care has changed to treating the morbidity and mortality of patients with COVID-19 and reducing medical procedures or visits to patients with HF, with the impact being greater in low- and middle-income countries. Methods: We performed an interrupted time series analysis of HF to determine the changes in the trend of hospitalizations and in-hospital mortality of HF patients before and after the mandatory lockdown in Peru. Results: A total of 18,514 adults were included in the analysis. Monthly hospital admissions immediately decreased by 599 (95% confidence interval [CI]: 113 to 1085) and the difference in slope before and after the lockdown was 6.4 hospital admissions (95% CI: −4 to 18). In-hospital mortality increased by 18% (95% CI: −8%–43%) and the difference in slope before and after the lockdown was −0.3% (95% CI: −0.9%–0.25%). Conclusions: There was a reduction in hospitalizations and an increase in the in-hospital mortality of patients with HF before and after the mandatory lockdown due to the COVID-19 pandemic in Peru.